Exploring the Efficacy and Safety of a Nursing Gel Formulation in Pregnant and Lactating Women With Cracked and Painful Nipples: An Open-Label, Single-Arm Clinical Study - Trupti Patel; Ramesh Prajapati; Virendra Narkhede M.; Rutu Bhimani; Tejas Vyas; Mrityunjay Tiwari (Journal of Human Lactation, 2026)
Background: Breastfeeding women often experience nipple pain, usually caused by incorrect newborn positioning in the first 10 days after childbirth. Aim: To explore the efficacy and safety of a novel gel-based formulation in healthy pregnant and lactating women with cracked and painful nipples. Method: Sixty participants were instructed to gently apply approximately 0.5 g of test product onto the nipples and surrounding area for 14 days (an open-label, single-arm study). Nipple pain, nipple skin physical parameters, skin hydration, and skin barrier function were assessed at various time points. Results: The nipple pain significantly reduced at all visits following the application of the test product, with a 43.7% decrease by 24 hours (Day 2; p < 0.0001) and a complete relief at Day 14 ( p < 0.0001) after application of the test product compared to the baseline. The dermatological assessment of nipple skin conditions revealed a significant improvement in dryness, nipple skin roughness, nipple skin redness/erythema, burning, itching, and stinging at all visits compared to the baseline. Skin hydration significantly improved by 23.55% by 24 hours ( p < 0.0001) and 42.25% at Day 14 ( p < 0.0001) as compared to baseline. Additionally, trans-epidermal water loss (TEWL) significantly reduced by 8.78% by 24 hours ( p < 0.0001) and 21.52% at Day 14 ( p < 0.0001) as compared to baseline. Conclusion: The gel-based formulation was well-tolerated and safe, with participants showing marked improvement in nipple symptoms within 24 hours and complete resolution by Day 14. These findings are preliminary and further controlled studies are needed to confirm the results. Clinical trial registry name: Clinical Trials Registry–India URL: www.ctri.nic.in . Registration number: CTRI/2022/08/044645